Letter (copy) : International Solidarity Fund - Citrine, Walter, 1887-1983
028-0166-001 P/V. WMC/HVT/FC/EK/136. 29th October, 1936. Mr. J. Price, Labour and Socialist International, 162, rue de Laeken, Brussels, Belgium. Dear Mr. Price, INTERNATIONAL SOLIDARITY FUND. Many thanks for your letter of the 23rd instant and for the information in regard to the further supplies which are being sent to Spain. Yours sincerely, General Secretary. 292/946/28/166